(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
An overview of recent advancement in the production of activated carbon (AC) from biomass using microwave heating is presented. The use of microwave heating method for the thermal conversion of biomass to useful products has been on the increase in the last decade because it offers fast and uniform heating, and a higher level of automation. The effects of process parameters (microwave power and radiation time, agent flow rate in physical activation and impregnation ratio in chemical activation) on the properties and adsorption capacity of the AC are reviewed. From the results reported in the literature, it can be seen that the influence of the preparation parameters on the adsorption capacity of the prepared AC followed the same pattern. In the physical activation process, microwave power and radiation time have more pronounce effects on the properties of the AC than the activation agent flow rate. Furthermore, the properties of the AC were found to be at their best when the process parameters are at the optimum values wether individually or collectively, and further increase in the process value beyond optimum value resulted in decrease in their adsorption capacity.